Fabrication of Active Z-Scheme Sr2MgSi2O7: Eu2+, Dy3+/COF Photocatalyst for Round-the-Clock Efficient Removal of Total Cr - Meng Xu; Junshu Wu; Mupeng Zheng; Jinshu Wang (Molecules, 2024)
Photoreduction is recognized as a desirable treatment method for hexavalent chromium (Cr(VI)). However, it has been limited by the intermittent solar flux and limited light absorption. In this work, a novel Z-scheme photocatalyst combining a covalent organic framework (COF) with Eu2+, Dy3+ co-doped Sr2MgSi2O7 (Sr2MgSi2O7:Eu2+, Dy3+) is synthesized, which shows the high spectral conversion efficiency and works efficiently in both light irradiation and dark for Cr(VI) reduction. Sr2MgSi2O7:Eu2+, Dy3+ serves as both an electron transfer station and active sites for COF molecule activation, thus resulting in 100% photoreduction of Cr(VI) (50 mL, 10 mg/L) with high light stability and over 1 h dark activity. Moreover, the XPS and FT-IR analyses reveal the existence of functional groups (Si-OH on Sr2MgSi2O7:Eu2+, Dy3+, and -NH- on COFTP-TTA) on the composited catalyst as active sites to adsorb the resultant Cr(III) species, demonstrating a synergistic effect for total Cr removal. This work provides an alternative method for the design of a round-the-clock photocatalyst for Cr(VI) reduction, allowing a versatile solid surface activation for establishing a more energy efficient and robust photocatalysis process for Cr pollution cleaning.